Analysis of ballistic and quasi-ballistic hole transport properties in germanium nanowires based on an extended "Top of the Barrier" model. (September 2016) - Tanaka, Hajime; Suda, Jun; Kimoto, Tsunenobu
Highlights: A simple model for quasi-ballsitic carrier transport in nanowires was proposed. The ballistic and quasi-ballsitic hole transport in germanium nanowires was studied. Nanowire geometries with high hole transport capability were investigated. Abstract: The ballistic hole transport properties in rectangular cross-sectional germanium nanowire transistors with various geometries were studied based on the "Top of the Barrier" model. Then, by an extension of this model, the quasi-ballistic hole transport was discussed taking into account phonon and surface roughness scattering in the channel and source-to-drain direct tunneling. Among several nanowire geometries targeted in this study, the [1 1 0]-oriented nanowire with large height along [1 1 ¯ 0] ([1 1 0]/(1 1 ¯ 0) NW) exhibited the largest ballistic current. This was understood from its large density of states and resulting high hole density. Large density of states, however, enhances backscattering in the channel. An approximation analysis of quasi-ballistic transport suggested that the [1 1 0]/(0 0 1) NW with higher mobility can outperform [1 1 0]/(1 1 ¯ 0) NW when scattering and tunneling are considered.